Migrant Care’s Role in Advocating the Educational Needs of Migrant Workers’ Children - Irma Indrayani Arief (AL-ISHLAH: Jurnal Pendidikan, 2021)
Education is a fundamental human need and a right of every citizen. Indonesia is one of the origin countries for many migrant workers. There is a complex problem with migrant workers, one of which is the education of migrant workers' children. Numerous civil society organizations, including Migrant Care, advocate for the rights of migrant workers. The purpose of this study is to examine Migrant Care's role in advocating for the educational needs of children of migrant workers and to analyze the factors that support and obstruct Migrant Care's ability to perform its function. The research method is qualitative-descriptive, with data being gathered via interviews and literature review. Data analysis begins with collecting data from various sources, which is then described and validated. This study makes use of role theory, interest groups, and systems theory. The findings of this research are Migrant Care's efforts to obtain official documents for migrant workers and to lobby the government for Community Learning Centers (CLC).